The Method for Solving the Split Equality Variational Inequality Problem and Application: Chinda Chaichuay, Atid Kangtunyakarn - Team, Support (Thai Journal of Mathematics, 2021)
Some method is introduced to solve the split equality variational inequality problem and we also apply our result to find solution of the split equality fixed problem and the null point problem of maximal monotone which are introduced by Moudafi and Al-Shemas [A. Moudafi, E. Al-Shemas, Simultaneous iterative methods for split equality problem, Trans. Math. Program. Appl. 1 (2013) 1-11] and Chang and Agarwal [S.S. Chang, R.P. Agarwal, Strong convergence theorems of general split equality problems for quasi-nonexpansive mappings, Journal of Inequalities and Applications 2014 (2014) 367], respectively.